ANALYSING THE MAIN COMPONENT STRUCTURE OF THE SURFACE WIND FIELD OF THE SOUTH CHINA SEA BY METHOD OF EMPIRICAL ORTHOGONAL FUNCTION ANALYSIS - Tuan, Nguyen van; Lanh, Vo Van; Son, Tong Phuoc Hoang (Vietnam Journal of Marine Science and Technology, 2008)
The paper presents the results of analyzing the main component structure of the surface (at the height of’ 10 m above sea surface) wind field of the South China Sea by method of Empirical Orthogonal Function analysis. The used dataset is collection of mean monthlv wind data for the meshes of 0.250 × 0.250 of all South China Sea during 8 years from 1999 to 2007. The results of analyzing indicated that the surface wind field of the South China Sea can be approximated by following 4 main components: - The first component EOF 1 is characterized for surface wind field in the season of the North - East monsoon with the existence of the strong wind divergence causing the strong water upwelling in the region north - west of the Luzon Island, and the strong wind convergence causing strong water downwelling in the region east of the Central and South Vietnam. - The second component EOF2 is characterized for surface wind field in the season of the South - West monsoon with existence of strong wind divergence causing strong water upwelling in the region east of the Central and South Vietnam. - The third and fourth components EOF3 and EOF4 are characterized for surface wind field in the transitional seasons with existence of West wind in central part of the South China Sea and the wind divergence in the region west of the Luzon Island, and the wind convergence in continental shelf of the south part of the South China Sea. - Other components are small and unstable, that can be neglected